Comparative Pharmacokinetic Investigation on Multiple Active Aminoalcohol-Diterpenoid Alkaloids after Single Oral Administrations of Monomers and Aqueous Extract of Fuzi (Aconiti Lateralis Radix Praeparata) by UFLC-MS/MS - Tang, Ming-Hai; Peng, Fu-Li; Liu, Xiu-Xiu; Chao, Ruo-Bing (Planta Medica, 2023)
To further study the aminoalcohol-diterpenoid alkaloids (ADAs) in Fuzi (Aconiti Lateralis Radix Praeparata), a simple and sensitive UFLC-MS/MS method was established and validated for the determination of five ADAs, aconine, mesaconine, hypaconine, deoxyaconine and fuziline, in rat plasma to compare the pharmacokinetic characteristics of pure ADAs and Fuzi decoction. After precipitating protein with methanol, plasma samples were isolated at 0.5 mL/min flow rate on Waters Acquity UPLC BEH C18 column (100 mm × 2.1 mm, 1.7 µm). The mobile phase was composed of 0.1% formic acid-water and methanol with gradient elution. Mass spectrometric inspection was conducted on a 5500 UFLC-MS/MS system with an electrospray ionization source in patterns of positive ion and multiple reaction-monitoring (MRM). All calibration curves were proved to have acceptable linearity (r2 > 0.99) in linear ranges. Intra-day and inter-day precision and the accuracy met the requirements. The matrix effects of all analytes were between 85% and 115% of three concentration levels. This method has been under verification for comparative pharmacokinetic research after oral administration between aqueous extract of Fuzi and single pure ADAs. The results demonstrated that there are evident pharmacokinetic discrepancies between them, and administration in the extract form instead of pure form may contribute to higher absorption.
Keywords: aminoalcohol-diterpenoid alkaloids; pharmacokinetics; aqueous extract of Fuzi; UFLC-MS/MS; Aconitum carmichaelii; Ranunculaceae